PENDIDIKAN RESPONSIF GENDER DI KABUPATEN ROKAN HILIR - Achmad Hidir; Nur Laila Meilani; Harapan Tua RFS (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The main cause of the gender gap in education is a lack of commitment and understanding of gender in Rokan Hilir (Hidir & Yanis, 2015). This study aims to (1) implement/apply the model of community empowerment-based design thinking in order to achieve gender-responsive education in Rokan Hilir; (2) to formulate gender-responsive educational design that is contextual in Rokan Hilir. This study uses a qualitative method variant in the form of phenomenology. The unit of analysis is the institutional community of the Department of Education and educators as well as educators in Rokan Hilir. The data collection technique uses the techniques of Participatory Rural Appraisal (PRA) with data analysis techniques in the form of a three-lane qualitative data analysis, namely data reduction, data display, and conclusion. The results showed that the application of design thinking allows for the application of social change, especially the mindset of the target group in a bottom-up manner. This means that the commitment and understanding of gender-responsive education could be increased from the root (grass root) without imposing target groups to change the values of the original locality of the region. Therefore, community empowerment is done to encourage social changes in a smooth and constructive manner for local development in Rokan Hilir, especially in the field of education and gender.